Efeitos de um programa de habilidades sociais comunicativas para crianças com distúrbio específico de linguagem - Carlino, Fabiana Cristina (2012)
The language is considered the first form of socialization of the child, and, in most cases, is done explicitly by parents through verbal instructions during daily activities. Thus, the child has access, even before learning to speak, the values, beliefs and rules, by contacting the concepts of their culture. However, some children experience serious difficulties in the acquisition and development of it. The Specific Language Impairment (SLI) is a change that has piqued the interest of many researchers due to its particularity, which refers to the great difficulty in developing language skills in the absence of auditory impairments, motor, mental retardation, neurological damage, comprehensive developmental disorders, acquired brain insults, restricted social interaction, behavioral disturbances, and emotional significance. The present study aimed to: a) assess the effects of an HSC program for a group of children with Specific Language Impairment (SLI), b) analyze the performance of each participant in this program, as indicators obtained preoperatively and post-intervention and c) to verify positive change reliable components Communicative Social Skills group and individually. Participants were eight children, between seven and nine years and eleven months of chronological age, both genders, with SLI. Data collection was divided into five phases: Preliminary - Contact those responsible; Phase I - Evaluation pre-intervention; Phase II - Planning and implementation of the intervention program; Phase III - Evaluation postintervention; Phase IV - Guidance and evaluating judges. Statistical analysis was based on the JT method, which aims to evaluate the pre-and post-intervention participants as a group and individually. The results suggested: reliable positive changes in the components of verbal and nonverbal content, but not reliably positive change was observed in verbal form. As the evaluation of the family QAP, P1, P2, P6 and P7 were participants more positively evaluated. While the evaluation of DC, the best participants were evaluated P3, P4, P5 and P8. It discusses the contributions of the study in terms of knowledge produced from steps taken, decisions and challenges of research and the 6 importance of investment in research in the area, involving the construction, adaptation and improvement of assessment tools for HSC DEL.